NEW RHYNCHOLITES OF THE SUBGENUS CONVEXITERBECCUS FROM THE LOWER CRETACEOUS OF THE SOUTHWESTERN CRIMEA - Komarov V.N. (My University, 2004)
New rhyncholite species Hadrocheilus (Convexiterbeccus) expressus, H. (C.) burshteini, H. (C.) kachensis, H. (C.) geniatus, and H. (C.) inexpectatus are described from the Upper Barremian and Aptian beds in the vicinity of the village of Verkhorech'e in the Southwestern Crimea.
Keywords: rhyncholite; Mesozoic::Cretaceous; Мезозой::Меловая